2021
DOI: 10.1017/jfm.2021.890
|View full text |Cite
|
Sign up to set email alerts
|

Bubble production by air filament and cavity breakup in plunging breaking wave crests

Abstract: Air filaments and cavities in plunging breaking waves, generically cylinders, produce bubbles through an interface instability. The effects of gravity, surface tension and surface curvature on cylinder breakup are explored. A generalized dispersion relation is obtained that spans the Rayleigh–Taylor and Plateau–Rayleigh instabilities as cylinder radius varies. The analysis provides insight into the role of surface tension in the formation of bubbles from filaments and cavities. Small filaments break up into bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
(123 reference statements)
2
21
0
Order By: Relevance
“…Garrett, Li & Farmer (2000) proposed that, for bubbles larger than the Hinze scale, a power-law scaling N(d) ∝ d −10/3 describes the steady-state bubble size distribution, assuming that the break-up rate scales with the turbulent frequency at the bubble size. This regime has since been reported in several experiments (Deane & Stokes 2002;Rojas & Loewen 2007;Blenkinsopp & Chaplin 2010) and simulations (Deike, Melville & Popinet 2016;Wang, Yang & Stern 2016;Soligo, Roccon & Soldati 2019;Chan et al 2021;Gao, Deane & Shen 2021;Rivière et al 2021;Mostert, Popinet & Deike 2022). For smaller bubbles, the size distribution typically exhibits a shallower slope (Deane & Stokes 2002;Blenkinsopp & Chaplin 2010), with fewer studies resolving this range of scales and some variation in the values that have been reported.…”
Section: Bubble Break-up In Turbulencesupporting
confidence: 57%
See 1 more Smart Citation
“…Garrett, Li & Farmer (2000) proposed that, for bubbles larger than the Hinze scale, a power-law scaling N(d) ∝ d −10/3 describes the steady-state bubble size distribution, assuming that the break-up rate scales with the turbulent frequency at the bubble size. This regime has since been reported in several experiments (Deane & Stokes 2002;Rojas & Loewen 2007;Blenkinsopp & Chaplin 2010) and simulations (Deike, Melville & Popinet 2016;Wang, Yang & Stern 2016;Soligo, Roccon & Soldati 2019;Chan et al 2021;Gao, Deane & Shen 2021;Rivière et al 2021;Mostert, Popinet & Deike 2022). For smaller bubbles, the size distribution typically exhibits a shallower slope (Deane & Stokes 2002;Blenkinsopp & Chaplin 2010), with fewer studies resolving this range of scales and some variation in the values that have been reported.…”
Section: Bubble Break-up In Turbulencesupporting
confidence: 57%
“…This regime has since been reported in several experiments (Deane & Stokes 2002; Rojas & Loewen 2007; Blenkinsopp & Chaplin 2010) and simulations (Deike, Melville & Popinet 2016; Wang, Yang & Stern 2016; Soligo, Roccon & Soldati 2019; Chan et al. 2021; Gao, Deane & Shen 2021; Rivière et al. 2021; Mostert, Popinet & Deike 2022).…”
Section: Introductionmentioning
confidence: 57%
“…Finally, the air bubbles reach the upper water surface and degas, whereas the thin filaments break into tiny bubbles. This is a clear manifestation of the Rayleigh-Taylor instability mechanism involving gravity and surface tension (Gao, Deane & Shen 2021b).…”
Section: Air Entrainment and Bubbles Distributionmentioning
confidence: 85%
“…Finally, the air bubbles reach the upper water surface and degas, whereas the thin filaments break into tiny bubbles. This is a clear manifestation of the Rayleigh–Taylor instability mechanism involving gravity and surface tension (Gao, Deane & Shen 2021 b ).
Figure 12.Details of the fragmentation of the cylindrical air cavity in numerical simulation of wave breaking at (3D1E4f).
…”
Section: Numerical Simulation Of Wave Breakingmentioning
confidence: 94%
“…Admittedly, we have assumed that the wave surface elevation is a single‐valued function, which may not be true when wave breaking occurs. However, to address this issue, high‐resolution observational data (e.g., Deane & Stokes, 2002; Erinin et al., 2019; Veron et al., 2012) or computationally expensive multi‐phase simulations (e.g., Gao et al., 2021; Tang et al., 2017) are needed to provide the hydrodynamic information of breaking waves, sprays and bubbles, which is beyond the scope of this study. Finally, we remark that our framework can be easily extended to more general parameter settings.…”
Section: Discussionmentioning
confidence: 99%